Therapeutic Effect of Polyherbal Formulation in The Management of Tamaka Śwāsa (Bronchial Asthma) - Pegu, Rigom; Yim, Mukamchem; Sarma, Bishnu Prasad (British Journal of Healthcare and Medical Research, 2023)
Tamaka Śwāsa is one among the 5 different respiratory disorders described elaborately in classics of Ayurveda having close resemblance to Bronchial Asthma. With time several polyherbal formulation modalities are found to be well-accepted, safe and effective in asthma due to multiple blocking and homeostasis of very complex, interdependent cellular, mediator networks supporting and involved in the inflammatory process. An open clinical trial was conducted with polyherbal formulation on 100 patients at Government Ayurvedic College & Hospital, Guwahati, Assam-781014,India to assist the therapeutic effect in the management of Tamaka Śwāsa (Bronchial Asthma). The therapeutic effect showed statistically extremely satisfactory relief symptomatically along with improvement in Peak Expiratory Flow Rate, Breath Holding Time to be statistically highly significant suggestive of bronchodilator effect and statistically reduction in ESR, AEC showed anti-allergic, anti-inflammatory effect. During the course of the clinical study of the trial drug no adverse reaction or side effect was observed in any of the patients and overall therapeutic response was encouraging. Thus, it is found that the polyherbal formulation is safe and ideal in the management of Tamaka Śwāsa (Bronchial Asthma).